Upaya rehabilitasi DAS Citarum dengan desain lanskap (studi kasus: bantaran sungai Citarum Desa Bojongsoang, Bandung dan Desa Purwadana, Karawang) - Ilhami, Wasissa Titi; Affandy, Andy (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018DO - 10.24843/JAL.2018.v04.i01.p13, 2018)
Landscape design employment to Citarum watershed rehabilitation (case study in Bojongsoang Village, Bandung Regency and Purwadana Village, Karawang Regency). Citarum watershed in Karawang and Bandung Regencies is a prone flooding area. An ideal landscape planning is required to manage this watershed area. It should be a conservation area that can be used by the community in surrounding both for recreation purpose when there is no flood and as a pick up point purpose during the flood. This research aimed to create technical design for the rehabilitation effort of river in Purwadana Village, Karawang Regency and Bojongsoang Village, Bandung Regency. It is expected that it can be used as an alternative design that can make people more adaptive to flood disaster. The management of watershed can be used for conservation area and river tourism. This tourism aims to make people care to their environment, to grow their sense of belonging to jointly maintain and conserve the river around their livelihood. Methods used in this research were survey method, land suitability analysis, interview, and literature study. The research results showed that according to the ecological analysis and ideal landscape approach for watershed area, this Citarum Watershed area is suitable for tourism site.